Real Effective Exchange Rate Misalignment in the Euro Area: A Counterfactual Analysis - Makram El-Shagi; Axel Lindner; Gregor von Schweinitz (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2014)
Were real effective exchange rates (REER) of Euro area member countries drastically misaligned at the outbreak of the global financial crisis? The answer is difficult to determine because economic theory gives no simple guideline for determining the equilibrium values of real exchange rates, and the determinants of those values might have been distorted as well. To overcome these limitations, we use synthetic matching to construct a counterfactual economy for each member as a linear combination of a large set of non-Euro area countries. We find that Euro area crisis countries are best described by a mixture of advanced and emerging economies. Comparing the actual REER with those of the counterfactuals gives sensible estimates of the misalignments at the start of the crisis: All peripheral countries were strongly overvalued, while high undervaluation is only observed for Finland.
urn:nbn:de:gbv:3:2-28859
Keywords: C22; F41; G14; 330; REER misalignment; Euro breakup; synthetic matching